ACG Clinical Guideline: Primary Sclerosing Cholangitis. (May 2015) - Lindor, Keith D; Kowdley, Kris V; Harrison, Edwyn M
Abstract : N/A: Primary sclerosing cholangitis is a chronic cholestatic liver disease that can shorten life and may require liver transplantation. The cause is unknown, although it is commonly associated with colitis. There is no approved or proven therapy, although ursodeoxycholic acid is used by many on an empiric basis. Complications including portal hypertension, fat‐soluble vitamin deficiency, metabolic bone diseases, and development of cancers of the bile duct or colon can occur.